THE LEVEL OF URGENCY OF COMMUNITY-BASED ECONOMIC DEVELOPMENT (CBED) IMPLEMENTATION: DETERMINANT AND THEIR INFLUENCE ON THE PERFORMANCE OF WEAVING CRAFT MICRO-BUSINESSES ON LOMBOK ISLAND, WEST NUSA TENGGARA - Dyah Mieta Setyawati; Kartawan Kartawan; Sudaryanto Sudaryanto (Journal of International Conference Proceedings (JICP), 2019)
The use of resources for women of Sasak Tribe as weaving producers in weaving centers spread across four regencies of Lombok Island has not been able to determine the level of urgency for the implementation of CBED for the weaving micro business community. This study aims to analyze the influence of community level empowerment, business strengthening and community characteristics on the level of urgency of CBED implementation and the influence of the level of urgency of CBED implementation on the performance of weaving craft micro-businesses on Lombok Island. This research method used is a survey method, which is confirmatory research which aims to explain the causal relationship between variables. Data was taken through observation and direct interviews with 200 respondents in 2017 using a questionnaire then processed using SPSS Statistics version 22 software. The sample was selected by probability sampling technique which was purposive sampling in four districts on Lombok Island. The analysis was carried out descriptively and verificative, by testing hypotheses on community level empowerment factors, business strengthening, community characteristics, the level of urgency of CBED implementation, business performance using Structural Equation Modeling analysis and processed with AMOS version23 software. The result of the research indicate, that Community Level Empowerment (PTK) influences the level of urgency of CBED implementation by 0,165 with the key factors are competent community and strong leadership. Business Strengthening (PU) does not influences the level of urgency of CBED implementation. The Characteristics of the Community (KK) influences the level of urgency of CBED implementation by 0,225 with the key factors are intangible assets and business capabilities. The level of urgency of CBED implementation does not influences Business Performance (KU). The result of the study revealed that the Characteristics of the Community (KK) were the dominant factors which had influences on increasing the level of urgency of CBED implementation. Determinant factors of the level of urgency of CBED implementation in weaving craft micro-enterprises are factors from the dimension of competent community and leadership (PTK) and factors from intangible assets and business capabilities (KK).